2016
DOI: 10.3109/10428194.2015.1118476
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility following dose-adjusted EPOCH-R chemotherapy in primary mediastinal B-cell lymphomas

Abstract: We assessed fertility/gonadal function in premenopausal women treated with dose-adjusted EPOCH-Rituximab for untreated primary mediastinal B-cell lymphoma (PMBL). Eligible patents were ≤ 50 years and premenopausal. Serial reproductive histories were obtained and hormonal assays were performed on serum samples before, at the end of treatment and 4-18 months later. Twenty-eight eligible women had a median age (range) of 31 (21-50) years and were followed a median of 7.3 years. Of 23 patients who completed a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The opportunity to discuss fertility preservation techniques should be considered for female patients but commonly this is not feasible because of the mode of presentation (De Vos et al , ; Yasmin et al , ). Whilst the rate of infertility in young patients treated with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone) may be relatively low (Elis et al , ), the addition of extra chemotherapy agents may affect the rate of infertility or premature ovarian failure and therefore the risks of each individual therapeutic regimen should be discussed with the patient (Gharwan et al , ).…”
Section: Fertility and Pregnancymentioning
confidence: 99%
“…The opportunity to discuss fertility preservation techniques should be considered for female patients but commonly this is not feasible because of the mode of presentation (De Vos et al , ; Yasmin et al , ). Whilst the rate of infertility in young patients treated with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone) may be relatively low (Elis et al , ), the addition of extra chemotherapy agents may affect the rate of infertility or premature ovarian failure and therefore the risks of each individual therapeutic regimen should be discussed with the patient (Gharwan et al , ).…”
Section: Fertility and Pregnancymentioning
confidence: 99%
“…Respondents reported evaluating male gonadal function after a median of 6 months (range, 3-12) from end of chemotherapy in 28 (48.3%) centers; evaluation included semen analysis (15.5%); FSH, luteinizing hormone, and testosterone levels (3.4%); and both semen analysis and hormonal evaluation (60.7%). Respondents reported assessing male gonadal function, first after a median of 6 months (range, 3-18) from the end of chemotherapy; 25 centers performed the assessment after a median of 12 months (range, [6][7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The survey included 43 questions (Supplementary Table S1), including 5 demographic questions concerning participant center information on geographic location, hospital, and number of female and male patients treated annually for hematologic malignancies and in particular for lymphoma; 11 questions, for females and males, on patient information, organization of referral, access to fertility preservation services, barriers and challenges for fertility preservation procedures, and number of patient refusals; and 9 questions for females and 7 questions for males on fertility preservation options and time intervals between diagnosis, counseling, fertility preservation procedure, and start of cancer treatment. Fifteen questions were dichotomous (4,6,8,14,15,20,22,23,27,29,31,36,37,39,41) and for 4 of them space was provided for comments (5,9,28,32); 16 questions required as an answer a number or a percentage (1,2,3,10,11,16,17,18,25,26,33,34,38,40,43,44); 9 questions were multiple response where respondents could select one or more answers (7,12,13,19,21,24,30,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the rate of fulfillment of parenthood increased with increasing time since treatment termination, suggesting that fertility can be regained. Several studies reported that, depending on the gonadotoxicity of the therapy applied and the patients' age at the time of diagnosis, gonadal function may recover [37][38][39][40]. However, these studies also revealed that women are at high risk of premature menopause, which may hamper family planning in women receiving chemotherapy at higher age.…”
Section: Discussionmentioning
confidence: 99%